FT-IR spectroscopic investigations of benzidine and bipyridyls adsorbed on diatomite from Anatolia - Özer, N. M.; AKYÜZ, ZEKİ TANIL; AKYÜZ, SEVİM (Elsevier, 2001)
FT-IR spectra of benzidine (bnz), 2,2′-bipyridyl (2,2′-bpy) and 4-4′-bipyridyl (4-4′-bpy) adsorbed on natural diatomite from Kutahya-Alayunt (Anatolia, Turkey) have been investigated. Vibrational results indicate the presence of chemisorbed species. No physical sorbed species has been detected. Bnz and 2,2′-bpy treated diatomite samples were found to be coloured, whereas 4,4′-bpy treated diatomite was not altered in colour. The formation of cationic (bnz+ and bnz2+) or anionic (2,2′-bpy−) surface species has also been detected in the case of bnz or 2,2′-bpy treated diatomite, respectively.
Keywords: FT-IR; Diatomite; Adsorption; Benzidine; Bipyridyl